Maternal employment and children's outcomes: Evidence from Indonesia - Ervin Dervisevic; Maria C. Lo Bue; Elizaveta Perova (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Is maternal employment beneficial or harmful for child development? Maternal employment generates income, which is needed to provide core inputs for children's health and education. However, maternal employment comes at the cost of time spent with children, which is also a critical input into children's development. The net impact is therefore theoretically ambiguous. Maternal employment, through mothers' exposure to wider social networks and greater bargaining may also be associated with how the family uses income. In this paper, we estimate the causal impact of maternal employment on several measures of children's health and education in Indonesia. We mobilize several data sources to construct a dataset of more than 32,000 observations of children aged 6 to 18 and employ a two-stage least squares strategy exploiting exogenous changes in tariffs on female-intensive sectors. We find that maternal employment significantly improves both education and health outcomes.
Keywords: D1; J13; J22; O15; 330; child development; maternal employment; Indonesia